2017
DOI: 10.1002/pssa.201700581
|View full text |Cite
|
Sign up to set email alerts
|

Study of InGaN/GaN Multiple Quantum Well Solar Cells With Different Barrier Thicknesses

Abstract: InGaN/GaN multiple quantum well solar cells (MQW‐SCs) with different barrier thicknesses are investigated. By comparing both the material property and device performance, it is demonstrated within our study that thinner barrier thickness in MQW‐SCs favors the transport of photogenerated carriers, but may be also accompanied by larger leakage current. An optimal trade‐off depends on the suitable barrier thickness. In addition, it also indicates that inadequate p‐type doping and unique polarization field have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The combined effects of inferior material quality and thinner barriers of M40 leads to the larger dark current densities. 23,26) Further, it is found that increasing temperature leads to a reduction of minority carrier lifetime in part due to the thermal activation of defects, which leads to further carrier loss at high temperatures.…”
Section: Sample M40 (40 Mqws)mentioning
confidence: 99%
“…The combined effects of inferior material quality and thinner barriers of M40 leads to the larger dark current densities. 23,26) Further, it is found that increasing temperature leads to a reduction of minority carrier lifetime in part due to the thermal activation of defects, which leads to further carrier loss at high temperatures.…”
Section: Sample M40 (40 Mqws)mentioning
confidence: 99%
“…Due to the growth of InGaN/GaN MQWs along the polar GaN [0001] direction, in InGaN QWs the polarization-induced quantum-confined Stark effect (QCSE), reducing the luminescence efficiency of InGaN QWs as well as the energy of emitted photons, plays a crucial role in the luminescence characteristics of light-emitting devices, which has attracted high research interest [14][15][16]. Nevertheless, the GaN quantum barriers also affect the QCSE in InGaN QWs as well as the transport of carriers in the whole MQW active region, which may strongly influence the performance of the optoelectronic devices based on the InGaN/GaN MQWs [17,18]. Compared with blue and green lightemitting InGaN/GaN MQWs, in the violet ones the In composition in InGaN well layers is smaller; accordingly, the effective potential height of the GaN barriers is reduced, resulting in a more significant influence of GaN barriers on the characteristics of violet MQW-based devices [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This is conceivable because the incorporation of the SLs layer structure effectively releases the planar strain of GaN in the active region and enhances the carrier tunneling effect. [15][16][17][18] It is important to acknowledge that, the SLs structure can be used in SCs to enhance the photogenerated carrier transport capacity by effectively regulating the stress in the active region as well as the special carrier tunneling effect possessed by the SLs structure due to its thinner potential barriers. Therefore, it is a promising research field to use SLs structures instead of MQWs structures to enhance the carrier tunneling effect and thus enhance the performance of photovoltaic devices.…”
mentioning
confidence: 99%
“…In 2012, Lang et al 17 introduced a hypothesis that the carrier escape lifetime can be smaller than the composite lifetime by using a sufficiently thin potential barrier in the active region structure, which demonstrates that carrier tunneling dominates. In 2017, Cai et al 18 observed that a thinner potential barrier thickness facilitates photogenerated carrier transport as well as can be accompanied by higher piezoelectric polarization and leakage voltage which acts as a barrier for higher-efficient SCs. In 2021, Althib et al 19 fabricated light-emitting diodes (LED) with In 0.2 Ga 0.8 N/GaN SLs structure and observed that the efficiency of the LED increased with thinner the potential barrier due to resonant tunneling effects.…”
mentioning
confidence: 99%